Enthesitis Related Arthritis: A Single Center Experience - Demir, Selcan; Kasap Cüceoğlu Müşerref; Bilginer, Yelda (Acta Medica, 2021)
Objective: Enthesitis-related arthritis is a subtype of juvenile idiopathic arthritis category, characterized by enthesitis, arthritis, and the risk of axial involvement. We aimed to summarize the demographics, clinical, and laboratory findings of enthesitis-related arthritis patients and to identify the distinguishing features of enthesitis-related arthritis patients with HLA B27 positive compared to the patients who were HLA B27 negative. Materials and Methods: This retrospective study included patients with Enthesitis-related arthritis who followed up between 2015 and 2018. Demographical, clinical, and laboratory data were retrospectively reviewed from the patient files and computerized medical charts. Results: A total of 72 patients diagnosed with enthesitis-related arthritis were included in the study. The male/female ratio was 2.1/1. Fifty-three (73%) of them presented with peripheral arthritis. The most commonly affected joint was knee (81.1%), followed by the ankle (43%), hips (32%), and wrist (5%). HLA B27 was positive in 36 (50%) patients. During follow-up, the number of patients who developed enthesitis-related arthritis -associated uveitis was 8 (11.1%). During follow-up, 56 patients with inflammatory back pain and/or sacroiliac tenderness underwent spinal MRI. Ten (17.8%) patients had only thoracal and/or lumbar involvement, 18 (32%) had only sacroiliitis, and 9 (16%) patients had both of them on spinal MRI. In comparison with HLA-B27-negative children, HLA-B27-positive patients were more likely to have enthesitis (16 (44.4%) vs 8 (22.2%), p=0.046), MRI proven sacroiliitis (19 (52.7%) vs 8 (22.2%), p=0.031), MRI proven spinal involvement (13 (36.1%) vs 6 (16.6%), p=0.031), and uveitis (8 (100%) vs 0(0%), p=0.014). During follow up, 65/72 (90.2 %) of them needed disease-modifying antirheumatic drugs (DMARD), and 51/72 (70.8%) needed anti-tumor necrosis factor-α (TNF-α) therapy. Conclusion: We found that patients who were HLA-B27- positive had significantly more enthesitis, MRI-proven sacroiliitis, MRI-proven spinal involvement, and acute anterior uveitis, in comparison to patients who were HLA B27 negative. It is crucial to carefully assess those patients with concern for enthesitis-related arthritis to determine the expected prognosis and make therapeutic decisions appropriately.